BIBLIOGRAFIE, RECENSIONI, RASSEGNE - Citraro, Cinzia; Lettiero, Marisa; Manero, Manuela; Longobardi, Ferdinando; Giusti, Giuliana (Annali del Dipartimento di Studi Letterari, Linguistici e Comparati. Sezione linguistica, 2021)
-